Children in Judicial and Non-Judicial Proceedings: The ECHR and CJEU Jurisprudence - Drnovšek, Katja (Children’s Rights in Regional Human Rights Systems, 2024)
Historically, the procedural rights of children participating in judicial and other proceedings have received limited attention in the case law of the European Court of Human Rights (ECtHR) and the Court of Justice of the European Union (CJEU). The European Convention on Human Rights (ECHR) does not explicitly address the special protection of children involved in court proceedings, and while the Charter of Fundamental Rights of the European Union (the Charter) does, the CJEU rarely deals with the rights of underaged participants in proceedings as the primary consideration of the case. Consequently, the case law that examines relevant children’s rights is somewhat fragmented and narrowly focused. However, in recent decades, the shift towards a child-centric approach and the impact of numerous international instruments dedicated to safeguarding children’s rights, especially the Convention on the Rights of the Child, have heavily influenced the practice of both Courts.  This paper provides an overview and analysis of landmark cases and other significant cases adjudicated by the ECtHR and the CJEU that focus on defining the following rights of a child: to be heard in family matters, as derived from Art. 8 of the ECHR and Art. 24 of the Charter; selected aspects of the right to a fair trial under Art. 6 of the ECHR (i.e. the right to effective participation and access to a lawyer); the representation of a child in proceedings before the ECtHR. Acknowledging the varying competencies and objectives of both courts, greater emphasis is placed on the more comprehensive ECtHR case law, all while duly considering the relevant CJEU jurisprudence.Keywords:  children’s rights, minors in judicial proceedings, the right to be heard, the right to effective participation, access to a lawyer